Karta wyników kapitału relacyjnego jako instrument controllingu działalności marketingowej - Nowak, Marta (Relational equity scorecard as a tool of marketing controllership, 2006)
The achievement of strategic goals of a company depends on various groups of its internal and external stakeholders. A new definition of marketing provided by American Marketing Association states that not only client but also other groups of stakeholders should be incorporated into marketing activities as their target group. In those companies where marketing plays an important role, instruments of marketing controllership should be applied. And Relational Equity Scorecard is an instrument that is relevant when the company marketing focuses strongly on relationships with differentiated stakeholder groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 313-319